Predation bite-marks on a peirosaurid crocodyliform from the Upper Cretaceous of Neuquén Province, Argentina (Ameghiniana, 2010)
Bite marks and injuries caused by intraspecific predation or aggressive social behavior are uncommon in fossil vertebrates, and in the fossil record of suchian archosaurs they are extremely unusual. A peirosaurid crocodyliform collected from the Upper Cretaceous beds of the Neuquén Group (northern Patagonia, Argentina) shows abundant bite marks and injuries. These injuries are spread across all the preserved parts of the specimen, with the highest concentration of bite marks, perforations and breakage in the caudal region. Characteristics of these injuries are analyzed, and their possible origin and related taphonomic aspects are assessed. Results indicate that the injuries were not produced by intraspecific fighting, but probably by the predating action of a theropod dinosaur.MARCAS DE PREDACIÓN EN UN CROCODILIFORME PEIROSAURIDO DEL CRETÁCICO SUPERIOR DEL NEUQUÉN, ARGENTINA. El hallazgo de marcas de mordeduras y lesiones por predación o comportamiento social agresivo intraespecífico en vertebrados fósiles es poco frecuente. En el registro fósil de arcosaurios suquianos tales evidencias son extraordinarias. Aquí se reporta un crocodiliforme peirosáurido del Cretácico Superior del Grupo Neuquén (norte de Patagonia, Argentina) con abundantes marcas de mordeduras y lesiones. Estas heridas están localizadas en todas las partes preservadas del espécimen, con una alta concentración de mordeduras, perforaciones y roturas en la región caudal. En el presente trabajo, se analizan las características de las lesiones, y también sus posibles causas y los aspectos tafonómicos relacionados. Los resultados muestran que las mordeduras fueron hechas por la acción de un predador y no por peleas intraespecíficas